Efeito das ações antrópicas na qualidade da água da bacia do Riacho do Silva, em Maceió-AL - Silva, Valdir Martiniano Ferreira da (2011)
In the last twenty years, Maceió city has faced an unordered urbanization process due to unplanned increasement of the city inhabitant number and lack of planning, this fact has transformed the city landscape. The Riacho do Silva river basin is located right in the middle of the city urban area, this watershed has an area around 10 km2, it presents several social and environmental problems due to irregular housing occupation, especially in areas of acute slope and on the Riacho do Silva riverbanks. Human activities like untreated wastewater releasing in the water coarse and solids waste inappropriate disposal are the main causes to water quality degradation occurred in that river basin. In this work the goal is to study the main human activities (e.g. wastewater releasing, solid waste disposal, illegal deforestation and economic river sand exploitation) and their effects on the Riacho do Silva watershed water quality, during this work period was studied the local human activities considered social, environmental and economic important to the river basin, when were collected and analyzed the main parameters related to the quality and quantity of that river basin water. The study results allowed concluding that human activities in the river basin area lead to a deterioration of the watershed water quality along the time. Social and economic aspects reveal the local population picture, those people have no governmental and public assistance, this lack of public action indicates to be the main cause of the actual Riacho do Silva water quality.